Pengembangan Sistem Informasi Reservasi Dan Penjadwalan Lapangan Futsal Arton Berbasi Web - Alven Emanuel Harefa; Candra Ponus Harefa; Gregorius Andi Prasition Gea; Jurisman Waruwu (CV. SINAR HOWUHOWU, 2026)
Manual booking and scheduling processes at the Arton Futsal court frequently result in double-booking issues, inaccurate schedules, and inefficiencies for customers who must check availability directly on-site. This study aims to design and implement a web-based reservation and scheduling information system for Arton Futsal to streamline business operations and improve customer convenience. The research utilizes a Project-Based Research (PBR) approach with mixed methods, applying the Waterfall development model using PHP and MySQL. The authentication and authorization flow of the system defines two distinct user levels with specific login access: Admin (manager) and Member (customer). System evaluation was conducted through Black Box Testing, and user friendliness was measured using the System Usability Scale (SUS) questionnaire. The results indicate that the developed system successfully automates court scheduling, minimizes data duplication or overlaps, and provides real-time information on field availability, thereby enhancing administrative efficiency and user satisfaction.